Analisis Pola Asuh Orang Tua dalam Membentuk Kepribadian Introvert pada Anak Usia Dini - Yuni Sri Utami; Chitra Charisma Islami (Jambura Early Childhood Education Journal, 2021)
Parenting style is an attempt by parents to educate their children more effectively. The introvert personality directs the person to subjective experiences, focuses on the inner and private world where reality is present in observations, tends to be aloof, quiet/unfriendly, even antisocial. This study aims to determine the analysis of parenting styles in shaping children's introvert personality at TK PGRI I Ciniru. This research uses a qualitative approach. The sample in this study was five students of TK PGRI I Ciniru. The sampling technique in this study using the purposive sampling technique. Data collection techniques are through observation, interviews, and documentation. Data were analyzed descriptively qualitatively. Based on the data from the analysis, it was found that out of the five students, three students had authoritarian parenting, one student had democratic parenting, and one student had permissive parenting. From the interviews and observations from parents and teachers, three students who have authoritarian parenting tend to have an introverted personality compared to the other two students. Therefore, it can be concluded that parents with introverted children's character, namely parenting, have a parenting pattern. Authoritarian.